PENGARUH NAUNGAN KANOPI KARET (Hevea brasiliensis. L) PADA PERTUMBUHAN GANYONG (Canna indica. L) SEBAGAI TANAMAN SELA - Widyanto (Bioma, 2020)
Ganyong (Canna indica L.) is a multifunction herbaceous plant that has been used for conturies as food, animal feed, and a soil conservation plant. Its ability to growth well in low-light conditions provides an opportunity to use C. indica as an intercropping plant between rubber trees that are often unused in rubber plantations. This research observed the effect of the shade of rubber canopy to the growth of C. indica compared to those grown on an open or sun exposed ground near rubber plantations in Subang (West Java). The results showed that plant height, stem length, number of leaves, tajuk dry mass, and rhizomes dry mass ware significantly higher (p < 0.05) in C. indica grown under canopy, 129.9 cm, 82.9 cm, 7.5 leaves 28.1 gr, 65.4 gr, compared to C. indica grown on open area at subang, 49.9 cm, 23.5 cm, 4.6 leaves, 10.9 gr, 15 gr. The RGR, NAR LAR, and SLA of C. indica under the rubber canopy 2 g. cm-2 day-1, 2.05 cm2. g-1 day-1, 44.2 cm2.g-1, 360.6 cm2. g-1 These results support the recommendation to use C. indica as intercropping plants to utilize the idle areas under the rubber stands.